2018
DOI: 10.1590/0100-29452018473
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality attributes of low chilling requirement ‘Snowchaser’ blueberry cultivated in Brazil

Abstract: -In Brazil there are still few studies on the post-harvest quality of low-chill blueberry cultivars, which have been recently introduced in the country. 'Snowchaser' blueberries were evaluated during a six-day storage period regarding fruit physical and chemical properties, and its antioxidant capacity. During fruit storage there was an increased weight loss and maintenance of some skin color properties such as luminosity (L*) and b*, whereas the values of parameter a* decreased and chroma (C) values increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The TAC of Snowchaser has previously been reported for fruits cultivated in the South of Brazil (62.36 mg cy-3-O-glu/100g FW) [42]. Despite the fact that both the South of Brazil and Spain share a hot climate, total Snowchaser anthocyanin was six times higher when cultivated in Spain.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 68%
See 1 more Smart Citation
“…The TAC of Snowchaser has previously been reported for fruits cultivated in the South of Brazil (62.36 mg cy-3-O-glu/100g FW) [42]. Despite the fact that both the South of Brazil and Spain share a hot climate, total Snowchaser anthocyanin was six times higher when cultivated in Spain.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 68%
“…The authors also demonstrated that the bush's genotype has a significant effect on the anthocyanin profile, and that their concentrations vary between harvests. It is worth noting that some varieties currently under cultivation in Andalusia, such as Snowchaser, Emerald and Jewel, accumulated total anthocyanins ranging from 63-101 mg/100 g in other blueberry-producing regions [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the 'Emerald' blueberries, produced in a subtropical region without chilling, remained suitable for commercialization and consumption until 12 days after harvest. This is an important result, since, for 'Snowchaser' blueberries, belonging to the same group as 'Emerald', this period was of only 6 days (Jimenes et al, 2018). The fact that, in the present study, the fruit were manually harvested and directly placed in packaging for transport also helped to extend shelf life, since blueberries are extremely susceptible to mechanical damage, which leads to loss of firmness, decreasing fruit quality and shelf life (Xu et al, 2015).…”
Section: Resultsmentioning
confidence: 73%